235 Injury recidivism in paediatric off-road vehicle riders. (20th November 2022) - Mulligan, Christopher; Adams, Susan; Möller, Holger; Whyte, Tom; Soundappan, Soundappan SV; Brown, Julie
Abstract : Background/Aims: Off-road motorcycles and quad-bikes are an important cause of paediatric injury and hospitalisation. A small subset of riders have multiple crashes and hospitalisations, which poses a significant burden on the individual and healthcare system. Our aim was to identify characteristics and differences between those injured only once and injury recidivists. Methods: A retrospective, cross-sectional study using linked data was performed of children 0–16 years in New South Wales, Australia, from 2001–2018, hospitalised due to injury from an off-road vehicle crash. Cox proportional hazard models were performed to estimate the hazard ratios for the likelihood of repeat hospital admissions. Results: Of the total 6624 hospitalisations, there were 202 repeated admissions in 184 patients, the recidivism rate was 3%. This included 24 repeat admissions from quad-bikes (in 23 patients) and 178 repeat admissions from motorcycles (in 161 patients). Males were more likely to be recidivists than females (HR:3.1, p<0.01). Both motorcycles and quad-bikes riders were more likely to be re-injured on the same vehicle type (motorcycle HR:2.4, p=0.003; quad-bike HR:4.2, p=<0.001). Living in remote or very remote areas was associated with increased risk of being admitted for a subsequent quad bike injury (HR:3.5, p=0.02). Other demographic factors, body region of injury, injury severity, or type of injury did not affect the likelihood of recidivism. Conclusions: Paediatric off-road riders are frequently re-injured on the same vehicle as their initial crash. A better understanding of the circumstances and contexts of these crashes may help to better target injury prevention counter-measures for recidivist riders.